2021
DOI: 10.3389/fmolb.2021.711928
|View full text |Cite
|
Sign up to set email alerts
|

LRMP Associates With Immune Infiltrates and Acts as a Prognostic Biomarker in Lung Adenocarcinoma

Abstract: Background: Lymphoid-restricted membrane protein (LRMP) is an endoplasmic reticulum-associated protein that is expressed in a developmentally regulated manner in both B and T cell lineages. However, the role of LRMP in the growth, prognosis and immune infiltration in lung adenocarcinoma (LUAD) remains unclear.Method: The expression levels of LRMP mRNA in tumor and normal tissues were analyzed using Tumor Immune Estimation Resource 2.0 (TIMER 2.0) and Gene Expression Profiling Interactive Analysis 2 (GEPIA 2). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 60 publications
0
5
1
Order By: Relevance
“…Thereby, no obvious differences between normal lung and lung adenocarcinoma tissue in IRAG2 expression levels were observed [ 107 , 108 , 109 ]. This, however, is in contrast to the data of Jin et al, who detected a lower IRAG2 gene and protein expression in lung adenocarcinoma tissue [ 104 ]. It is also shown that an IRAG2 Pro537Leu nonconservative variation was linked with an inflammatory response in the lungs of several mouse strains [ 110 ].…”
Section: Functional Features Of Irag2contrasting
confidence: 99%
See 4 more Smart Citations
“…Thereby, no obvious differences between normal lung and lung adenocarcinoma tissue in IRAG2 expression levels were observed [ 107 , 108 , 109 ]. This, however, is in contrast to the data of Jin et al, who detected a lower IRAG2 gene and protein expression in lung adenocarcinoma tissue [ 104 ]. It is also shown that an IRAG2 Pro537Leu nonconservative variation was linked with an inflammatory response in the lungs of several mouse strains [ 110 ].…”
Section: Functional Features Of Irag2contrasting
confidence: 99%
“…Additionally, high IRAG2 expression correlated with an upregulation of immune checkpoints. Hence, IRAG2 could also be involved in the immunotherapy response of lung adenocarcinoma patients using checkpoint inhibitors [ 104 ].…”
Section: Functional Features Of Irag2mentioning
confidence: 99%
See 3 more Smart Citations